Gene expression in solitary fibrous tumors (SFTs) correlates with anatomic localization and NAB2-STAT6 gene fusion variants - Bieg, Matthias; Moskalev, Evgeny A.; Will, Rainer D.; Hebele, Simone; Schwarzbach, Matthias; Schmeck, Sanja; Hohenberger, Peter; Jakob, Jens; Kasper, Bernd; Gaiser, Timo; Ströbel, Philipp; Wardelmann, Eva; et al. (The American journal of pathology, 2021)
Solitary fibrous tumors (SFTs) harbor recurrent NAB2-STAT6 gene fusions, promoting constitutional up-regulation of oncogenic early growth response 1 (EGR1)-dependent gene expression. SFTs with the most common canonical NAB2 exon 4-STAT6 exon 2 fusion variant are often located in the thorax (pleuropulmonary) and are less cellular with abundant collagen. In contrast, SFTs with NAB2 exon 6-STAT6 exon 16/17 fusion variants typically display a cellular round to ovoid cell morphology and are often located in the deep soft tissue of the retroperitoneum and intra-abdominal pelvic region or in the meninges. Here, we employed next-generation sequencing-based gene expression profiling to identify significant differences in gene expression associated with anatomic localization and NAB2-STAT6 gene fusion variants. SFTs with the NAB2 exon 4-STAT6 exon 2 fusion variant showed a transcriptional signature enriched for genes involved in DNA binding, gene transcription, and nuclear localization, whereas SFTs with the NAB2 exon 6-STAT6 exon 16/17 fusion variants were enriched for genes involved in tyrosine kinase signaling, cell proliferation, and cytoplasmic localization. Specific transcription factor binding motifs were enriched among differentially expressed genes in SFTs with different fusion variants, implicating co-transcription factors in the modification of chimeric NGFI-A binding protein 2 (NAB2)-STAT6-dependent deregulation of EGR1-dependent gene expression. In summary, this study establishes a potential molecular biologic basis for clinicopathologic differences in SFTs with distinct NAB2-STAT6 gene fusion variants.
Gesehen am 09.06.2022